2014
DOI: 10.1038/ajg.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease or Non-Celiac Gluten Sensitivity? An Approach to Clinical Differential Diagnosis

Abstract: On the basis of our findings, we have developed a diagnostic algorithm to differentiate CD from NCGS. Subjects with negative celiac serologies (IgA tTG or IgA/IgG DGP) on a regular diet are unlikely to have CD. Those with negative serology who also lack clinical evidence of malabsorption and CD risk factors are highly likely to have NCGS and may not require further testing. Those with equivocal serology should undergo HLA typing to determine the need for biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 24 publications
3
50
0
12
Order By: Relevance
“…Unfortunately, much of the clinical world has not yet grasped the idea that gluten can trigger autoimmune disorders other than CD, which leads to misleading notions that only CD patients have to be strict with the gluten-free diet (GFD), while NCGS patients can "cheat" once-ina-while. Statements such as, patients with "NCGS can be more liberal and titrate their exposure to gluten as needed to avoid symptoms, " [53] can be harmful to the patient. CD is a gastrointestinal disorder in which patients make elevated IgA to gliadin and tissue transglutaminse-2.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, much of the clinical world has not yet grasped the idea that gluten can trigger autoimmune disorders other than CD, which leads to misleading notions that only CD patients have to be strict with the gluten-free diet (GFD), while NCGS patients can "cheat" once-ina-while. Statements such as, patients with "NCGS can be more liberal and titrate their exposure to gluten as needed to avoid symptoms, " [53] can be harmful to the patient. CD is a gastrointestinal disorder in which patients make elevated IgA to gliadin and tissue transglutaminse-2.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published diagnostic model (Figure 1) for symptoms responsive to a GFD by Kabbani et al can be very helpful in differentiating CD from NCGS. [154]. This model can be employed to differentiate between CD and NCGS after ruling out WA with IgE assays when it is suspected based on signs of an allergic etiology such as hives, urticaria, angioedema or eczema.…”
Section: Functional Assays (Fa) or Food Challenge Testmentioning
confidence: 99%
“…It has been suggested that where available negative human leucocyte antigen DQ2 and DQ8 genotype is useful, in that in can exclude CD with certainty given its 100 % negative predictive value; this will account for almost half of presenting cases (31) . However, if human leucocyte antigen-DQ typing is not readily available, or is positive, then a gluten challenge followed by coeliac investigations is required (46) . Traditionally, a gluten challenge has been suggested to be ≥10 g gluten (equivalent to about 4 slices of bread) daily for 6 weeks, prior to formalised testing.…”
Section: How To Diagnose Non-coeliac Gluten Sensitivitymentioning
confidence: 99%
“…To date, the reference standard for the diagnosis of 'true' NCGS is an elimination diet followed by double-blind placebocontrolled gluten challenge, a method which could hardly be introduced into clinical practice (11) . Recently, a diagnostic algorithm based on the absence or presence of clinical, serologic and histological criteria has been proposed to diagnose and differentiate NCGS from CD (46) . This novel study provides a clinically pragmatic approach as it takes into consideration the difficulties that arise when evaluating patients who present with gluten-based sensitivity and are already taking a GFD, which in cases of CD can lead to negative coeliac serology and normal duodenal biopsies (46) .…”
Section: How To Diagnose Non-coeliac Gluten Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation